Perinatal Outcomes in Babies Born before Arrival at Prince Mshiyeni Memorial Hospital in Durban, South Africa - M. Jenneker; N. R. Maharaj (Obstetrics and Gynecology International)
Objective. To evaluate the maternal demographics, incidence, perinatal outcomes, and characteristics of babies born before arrival (BBAs) to hospitals. Methods. A prospective, observational study was conducted at a large maternity unit in Durban, KwaZulu-Natal. A total of 200 mothers who attended the hospital within 24 hours of an out-of-hospital birth were recruited and interviewed, and 142 participants were eligible. A total of 128 mothers who delivered their babies in hospital (inborns) were used as the control group. Specific maternal and neonatal characteristics were analysed. Results. The incidence of BBAs was 2.2%. The percentage of premature neonates in the BBA group was 54% vs 17.9% for inborns (p≤0.001). A total of 33.8% of BBA mothers were unbooked vs 2.4% of inborns (p≤0.001). The majority (59%) of inborns were primigravidas whereas the majority (73.9%) in the BBA group were multigravidas (p≤0.001). Women in the BBA group were more prone to genital tears (p≤0.001). There were no significant differences in respect of NICU admission and all-cause mortality; however, an increased risk for hypothermia and hypoglycaemia was found. Conclusion. BBAs are at a significant risk of prematurity, low birth weight, hypothermia, and hypoglycaemia and are prone to longer hospital stays.